Diagnóstico socioeconômico e ambiental nas marmorarias do município de Pau dos Ferros-RN - Lauriano, Francisco Andtalys da Silva (Universidade Federal Rural do Semi-Árido, 2017)
In recent decades, Brazil has witnessed significant growth in the production of ornamental stones, shops that work with rocks for highly decorative ornamental uses, are called marble works. The objective of this study was to perform a socioeconomic and environmental diagnosis in the city of Pau dos Ferros / RN, through a description of the activities, processes and services of these enterprises. The methodological procedures of this research were: bibliographic research and data collection in survey. It was found that in Pau dos Ferros - RN, 50% of the companies have up to 9 employees (micro size), while 50% have 10 to 49 employees (small size), 50% have annual microenterprise income of 60,000.00 a R $ 360.00,00 and the other small ones have 360,000.00 to R $ 3,600,000.00. It was also verified that the main environmental impacts of these projects are related to the incorrect destination of inputs, water consumption, energy consumption, raw material and the generation of effluents and solid waste. It was evidenced that the proposals of environmental management guidelines provided improvements on the environmental evaluation of the enterprises, general aspects of the enterprises, uses of the natural resources and inputs by the enterprises and environmental analysis of the enterprises. Therefore, it is necessary to invest in actions that contribute to the improvement of this economic activity, to ensure the environmental legality of this commercial arrangement.
Keywords: Socioeconômico e Ambiental; Marmorarias; Legalidade Ambiental; Socioeconomic and Environmental; Marble Works; Environmental Legality; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA